2010
DOI: 10.1002/jctb.2505
|View full text |Cite
|
Sign up to set email alerts
|

Stability of cutinase, wild type and mutants, in AOT reversed micellar system—effect of mixture components of alkyl esters production

Abstract: BACKGROUND: Fusarium solani pisi cutinase was microencapsulated in reversed micelles of bis(2-ethylhexyl) sodium sulfosuccinate (AOT) in isooctane for the production of alkyl esters, known as biodiesel; its stability in this system was also evaluated. Results using cutinase wild type and three mutants, L153Q, T179C and S54D, were compared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…AOT has been shown to have an inactivating effect on cutinases. For example, the F. solani pisi cutinase (1 mg/mL) lost 45 % of activity, when incubated in reverse micelles of AOT at 30°C for 3 h. Methanol, which was used as the substrate in addition to triolein in the transesterification reactions studied, was also found to inactivate the cutinase; 90 % of enzyme activity was lost in the presence of 390 mM methanol already after 10 min (Badenes et al 2011b). AOT has been reported to cause a conformational change in the active site.…”
Section: Cutinases In Biocatalysismentioning
confidence: 97%
“…AOT has been shown to have an inactivating effect on cutinases. For example, the F. solani pisi cutinase (1 mg/mL) lost 45 % of activity, when incubated in reverse micelles of AOT at 30°C for 3 h. Methanol, which was used as the substrate in addition to triolein in the transesterification reactions studied, was also found to inactivate the cutinase; 90 % of enzyme activity was lost in the presence of 390 mM methanol already after 10 min (Badenes et al 2011b). AOT has been reported to cause a conformational change in the active site.…”
Section: Cutinases In Biocatalysismentioning
confidence: 97%
“…In the first case, 32 h recirculation, the conversion decreases to a residual value after starting the continuous mode, most likely due to a dilution effect, as the enzyme was already fully denatured. This denaturation is caused by the toxic effect that methanol has towards cutinase wild type, as already observed in batch incubation tests in the presence of methanol (Badenes et al, 2011). In the second case, the 3 h were not enough to reach a steady-state to ensure that the enzyme was adsorbed onto the membrane.…”
Section: Evaluation Of Cutinase Membrane Reactor Performance In Contimentioning
confidence: 87%
“…In previous work, mutants of cutinase were evaluated in terms of their activity in the reversed micellar system and their stability in the presence of AOT (Badenes et al, 2011). It was found that the cutinase mutant T179C has a high resistance to the denaturing effect of AOT, and, even more, it has a higher stability in the presence of methanol when compared with cutinase wild type.…”
Section: Evaluation Of Cutinase Membrane Reactor Performance In Totalmentioning
confidence: 98%
See 2 more Smart Citations